2020
DOI: 10.21873/invivo.11887
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Patella-baja and Pseudo-patella-baja Does Not Improve Range of Motion in Patients After Mega-TKA

Abstract: Background/Aim: Patella baja (PB) and pseudopatella baja (PPB) have been shown to negatively influence outcomes after total knee arthroplasty. We hypothesized that there is a high incidence of PB and PPB after megaprosthetic total knee arthroplasty (M-TKA), and that this is associated with reduced range of motion. Patients and Methods: We retrospectively analysed all patients in our Orthopaedic Trauma Department after distal femur or proximal tibia replacement. Preoperative and one-year postoperative followup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
2
2
Order By: Relevance
“…22–24 However, recent studies have shown that patella baja does not affect the patient’s postoperative ROM. 25 , 26 In our study, patella baja (P>0.05) was also not an influencing factor of squatting. Bellemans et al 27 defined a parameter termed “posterior condylar offset.” They found that PCO was associated with a postoperative change in flexion angle in CR knees, whereas this correlation was not observed in PS knees.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…22–24 However, recent studies have shown that patella baja does not affect the patient’s postoperative ROM. 25 , 26 In our study, patella baja (P>0.05) was also not an influencing factor of squatting. Bellemans et al 27 defined a parameter termed “posterior condylar offset.” They found that PCO was associated with a postoperative change in flexion angle in CR knees, whereas this correlation was not observed in PS knees.…”
Section: Discussioncontrasting
confidence: 45%
“…[22][23][24] However, recent studies have shown that patella baja does not affect the patient's postoperative ROM. 25,26 In our study, patella baja (P>0.05) was also not an influencing factor of squatting. Bellemans et al 27 defined a parameter termed "posterior condylar offset."…”
contrasting
confidence: 44%
“…There were also many reports in the literature that patella baja can restrict the ROM of the knee (21)(22)(23). However, recent studies had shown that patella baja doesn't affect the patient's postoperative range of motion (24,25). In our study, patella baja(P 0. the patients in our study were all PS knees, which also explained why PCO had no effect on the postoperative squatting ability in our ndings.…”
Section: Discussionmentioning
confidence: 42%
“…Outside of oncologic reconstructions, the indications to use a PTR are limited. In cases with insufficient support for reconstruction in zone 2, a PTR should be used as a last resort, given that outcomes and survivorship are worse when PTRs are used [26,77,83,93]. It should be noted that cases with complex and massive tibial bone loss may also have insufficient soft tissue coverage, and a muscle flap may be required for coverage in this area of a reconstruction to decrease the chances of failure secondary to wound breakdown.…”
Section: Panel 4: Considerations Regarding Complex Modular Replacemen...mentioning
confidence: 99%